2016
DOI: 10.1038/ni.3487
|View full text |Cite
|
Sign up to set email alerts
|

Control of the innate immune response by the mevalonate pathway

Abstract: Deficiency of mevalonate kinase (MVK) causes systemic inflammation. However, the molecular mechanisms linking the mevalonate pathway to inflammation remain obscure. Geranylgeranyl pyrophosphate (GGPP), a non-sterol intermediate of the mevalonate pathway, is the substrate for protein geranylgeranylation, protein post-translational modification catalyzed by protein geranylgeranyl transferase I (GGTase I). Pyrin is an innate immune sensor that forms an active inflammasome in response to bacterial toxins. Mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(181 citation statements)
references
References 45 publications
7
168
2
Order By: Relevance
“…However, the clinical efficacy of colchicine treatment is likely associated with its ability to decrease leukocyte motility and phagocytosis during inflammation (37,38). Recent studies suggested that defects in the mevalonate pathway seen in the hereditary autoinflammatory disease mevalonate kinase deficiency (MKD), also named "hyperimmunoglobulinemia D syndrome" (HIDS), may also trigger unwarranted activation of the Pyrin inflammasome (14,39). In contrast to FMF patients, however, MKD patients generally do not benefit from colchicine treatment, whereas blockade of IL-1 has shown promising results (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical efficacy of colchicine treatment is likely associated with its ability to decrease leukocyte motility and phagocytosis during inflammation (37,38). Recent studies suggested that defects in the mevalonate pathway seen in the hereditary autoinflammatory disease mevalonate kinase deficiency (MKD), also named "hyperimmunoglobulinemia D syndrome" (HIDS), may also trigger unwarranted activation of the Pyrin inflammasome (14,39). In contrast to FMF patients, however, MKD patients generally do not benefit from colchicine treatment, whereas blockade of IL-1 has shown promising results (40).…”
Section: Discussionmentioning
confidence: 99%
“…Our biochemical analysis of CD11c-enriched AdCre/KRAS G12D lung cells treated with atorvastatin showed decreased AKT, but not ERK, phosphorylation ( Figure 7C), suggesting that inhibition of RAS prenylation inhibits RAS interaction with phosphatidylinositol 3-kinase (PI3K), as reported for marrow-derived macrophages. 45 Of note, poly (ADP-ribose) polymerase 1 (PARP-1) cleavage was also induced by atorvastatin ( Figure 7C), indicating that apoptosis of atorvastatin-treated CD11c 1 cells might contribute to the reduced CD11c levels in atorvastatin cultures ( Figure 7B). The in vitro effects of atorvastatin prompted us to target the myeloid neoplasm in vivo.…”
Section: G12d -Driven Pulmonary Lch-like Disease In Mice 523mentioning
confidence: 94%
“…51 Our biochemical data ( Figure 7C) suggest that atorvastatin inhibits prenyl-dependent association between KRAS and PI3K as reported in simvastatin-treated human peripheral blood mononuclear cells. 45 Intriguingly, PIK3CA/BRAF comutations have been identified in Erdheim-Chester disease, a histiocytic disorder closely related to LCH, 52 suggesting that cooperative activation of the MEK/ERK and PI3K pathways could contribute to the pathogenesis of histiocytic neoplasms. Although cancer-associated PIK3CA mutations are rare in LCH, 53 we previously reported contribution of autocrine PI3K activation to the aberrant growth of BRAF V600E -expressing mouse HSPCs.…”
Section: Gr1mentioning
confidence: 99%
“…4A). Control of metabolic flux through the mevalonate pathway is of paramount importance for prevention of various diseases (Akula et al, 2016;Frenkel et al, 2000), and for the development of biobased production of pharmaceuticals, food additives, fuels, cosmetics and others (Ye et al, 2016). In yeast, ERG12 encodes the mevalonate kinase, responsible for phosphorylation of mevalonate, whereas ERG20 encodes farnesyl pyrophosphate synthase, which catalyzes the formation of both farnesyl pyrophosphate (FPP) and geranyl pyrophosphate (GPP), units for sterol and isoprenoid biosynthesis (Chambon et al, 1991;Oulmouden and Karst, 1990).…”
Section: Application Of Casper For Engineering Key Enzymes In Yeast Mmentioning
confidence: 99%